The Role of Financial Leverage and Cost Management on Operational Efficiency and Earnings Stability in Hospitality Industry in Indonesia - Afandy, Chairil (The Eastasouth Management and Business, 2024)
This study explores the impact of cost management and financial leverage on operational efficiency and earnings stability in the hospitality industry in Indonesia. Utilizing a quantitative approach, data was collected from 280 hospitality businesses and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that both cost management and financial leverage significantly contribute to earnings stability, with financial leverage also playing a strong role in improving operational efficiency. Operational efficiency serves as a critical mediator, linking financial strategies to stable earnings. The findings highlight the importance of carefully balancing debt financing and cost control to optimize both financial performance and operational processes in the hospitality sector. These insights offer valuable guidance for hospitality managers seeking to enhance long-term profitability and resilience in a highly competitive industry.